Evaluation and reduction of vulnerability of subway equipment: An integrated framework. (March 2018) - Deng, Yongliang; Song, Liangliang; Zhou, Jianliang; Wang, Jianping
Highlights: An integrated framework is put forward to study vulnerability of subway equipment. A vulnerability evaluation model is established based on GCA and TOPSIS. A variable weight evaluation model is established based on variable weight theory. Recommendations are proposed based on research results for promoting subway safety. Abstract: Subway system, consisted of a variety of equipment, is a fundamental and critical infrastructure providing basic transportation service for promoting social development. According to statistics, it is discovered that equipment fault is the main reason for interruptions or accidents in subway operation. Due to the serious results of equipment fault, equipment safety management should be proactive and effective. At first, an integrated framework is put forward for evaluation and reduction of vulnerability of subway equipment. Then, case study is implemented for demonstrating feasibility and effectiveness of the proposed framework in evaluating vulnerability in vehicle and assessing running status of wheel set. It is discovered that the two kinds of most vulnerable equipment in vehicle are train door and train control and management system. The running status of 24 detected wheel sets are identified based on variable weight theory. Finally, recommendations are proposed for reducing the vulnerability and promoting equipment safety management from two perspectives. The warning threshold is set as blue warning, yellow warning and red warning. The logic diagram of maintenance modes is presented in consideration of vulnerability, technology, economy and fault feature. The proposed framework has the potential for a better understanding of vulnerability of subway equipment, and this study may be beneficial to offer suggestions related to equipment safety management for reducing accident caused by equipment fault.